1994
DOI: 10.2307/3350295
|View full text |Cite
|
Sign up to set email alerts
|

Improving Health: Measuring Effects of Medical Care

Abstract: The impact of medical care on the quality and length of life of the population has been poorly documented. The rapid growth of evidence of efficacy of therapy for individual medical conditions now offers the opportunity to create an inventory of benefits. A method for creating such an inventory is described, as is its application to a selection of condition-treatment pairs, chosen for their high incidence of prevalence, their serious outcomes, and the demonstrated efficacy of their treatment. An aggregate effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
105
0
9

Year Published

1995
1995
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(116 citation statements)
references
References 45 publications
2
105
0
9
Order By: Relevance
“…Despite increasing demand for TKAs and cost-effectiveness of the procedure [11,16,17], a substantial number of patients who undergo a TKA are dissatisfied with the outcomes, with reported satisfaction rates varying between 75% and 89% [1,6,7,23,24,36,41,51], regardless of patient demographics or severity of disease.…”
Section: Introductionmentioning
confidence: 99%
“…Despite increasing demand for TKAs and cost-effectiveness of the procedure [11,16,17], a substantial number of patients who undergo a TKA are dissatisfied with the outcomes, with reported satisfaction rates varying between 75% and 89% [1,6,7,23,24,36,41,51], regardless of patient demographics or severity of disease.…”
Section: Introductionmentioning
confidence: 99%
“…When medical therapy fails to control pain or physical functioning reaches an unacceptable level, total joint arthroplasty (TJA) of the hip or knee is indicated (3,4). Although TJA results in substantial reduction in pain and disability (3)(4)(5)(6)(7), studies indicate that candidates for surgery can be reluctant to consider TJA. For example, in a US study, many African Americans with advanced knee osteoarthritis (OA) reported being unwilling to have surgery, reflecting a belief that it would not significantly improve their current health (8).…”
Section: Introductionmentioning
confidence: 99%
“…It is far from clear, however, that medicine can claim this much credit. An optimistic accounting of the benefits of specific treatments attributes only five years of the forty or more years of added lifespan over the last two centuries to medicine [17].…”
Section: Medicine and Healthmentioning
confidence: 99%